The Model of Family Counseling in Early Intervention Setting for Children with Special Needs - Sunardi, Sunardi (Department of Special Education, 2020)
The aim of this research is to formulate the model of the family counseling for children with special needs by making parenting stress as a major successful indicator. This research is conducted by qualitative approach through studying the cases deeply in Laboratory of Special Education Department, Faculty of Education, Indonesia University of Education, year 2016. In this research, ML and AH became cases where both of them are the parents of the children with special needs in early age. The result toward the case shows that the parents have already understood their children’s ability and inability but they have not understood their special needs and how to fulfill it. Then the result is they tend to worried and nervous even confused in treating their children related to take them care, their school, and they future. Whereas, the behavior, attitude and some efforts that appear along this time are not productive and harmony enough with their children’s special need even with the demand of their selves and environment, so it does not give significant effect for the children’s improvement and the decreasing parenting stress. However, even the obstacle learning and their children development are complex, but the parents are still optimist and they hope that one day, their children will growth as the normal children. According to that problems, the formula of the model family counseling to early age which is appropriate in reducing parenting stress that are facing by family with special needs children is the model that design by differentiating service by create interpersonal relationship, early intervention setting, group family support service, and home visit as the major pillar, is conducted by interdisciplinary approach and the expert as social support, and counselor’s responsibility as an ahead and coordinator of all given counseling service program. In fact, this model is still hypotetic, so to test its effectiveness have to be tested further.